SPK Rekomendasi Platform E-Commerce terbaik Menggunakan Metode (SAW) - saputra, made okta (Universitas Multi Data Palembang, 2024)
The rapid advancement of technology has significantly transformed modern economic life, particularly through e-commerce, which leverages digital tools and internet access. In Indonesia, e-commerce began in 1999 and experienced substantial growth in 2019 due to increased internet usage and smartphone adoption. Despite offering numerous benefits, users face challenges such as product price variations, product mismatches, and delivery issues. Decision Support Systems (DSS) using the Simple Additive Weighting (SAW) method have been proposed to determine the best alternative e-commerce platform. These systems provide accurate recommendations based on predefined criteria. The final scores indicate that the comparison between the system’s calculations and Microsoft Excel calculations showed 100% similarity. Shopee ranked first with a score of 0.95, making it the most suitable e-commerce platform solution